Digital Media-Based Interventions to Promote Healthy Lifestyles and Psychological Wellbeing of Nurses in Kenya - Njeru, Margaret (International Journal of Psychology, 2023)
Purpose: The purpose of this paper is to find out the effectiveness of applying digital media tools as an intervention to enhance the availability of information and resources related to mental health care to nurses and promote a healthy lifestyle. A growing number of health care workers suffer from mental health issues and poor psychological well-being. Many workers report cases of anxiety, burnout, and depression because of poor working conditions and unfavorable environments. Protecting health and well-being of care workers through integration of interventions aimed at increasing knowledge on mental health is one of the best strategies that could yield good outcomes for care givers. Nurses spend a large proportion of their lives in hospitals, hence, a need to create a healthy and safe working environment. Investing in a culture of managing and preventing mental health issues among the nursing staff by integrating modern approaches aimed at supporting education and training on mental health and psychological wellbeing remains a key agenda for the improvement of wellbeing of nurses. Emerging digital technologies such as social media, mobile-based and web-based applications have created new ways that individuals use to interact with one another, and could be very useful in creating awareness and enhancing knowledge on mental health and wellbeing of nurses. Majority of nurses have access to smartphones, which makes it easy to access mental health care through various mobile applications. Methodology: The study targeted nurses in Kenyan hospitals, with specific focus on public hospitals in Embu County. A quantitative research was conducted with a sample size of 100 nurses from level-4 and level-5 hospitals. 65 responses were collected. Findings: The outcome showed that majority of nurse have active social media channels and have been using them to learn more about mental health. Also, it was found out that using social media has a major role to play in increasing awareness on mental health among nurses, and it ensures nurses embrace a healthy lifestyle. Unique Contribution to Theory, Practice and Policy: Findings from the study are of great significance towards developing interventions and policy approaches for promoting healthy lifestyle and improving psychological wellbeing of nurses. Also, the outcome would be of help in developing policy frameworks for managing and preventing mental health among health workers.